Analysis of Dust Storm Intensity over Baghdad City - Asmaa K. Hammoodi; Ahmed S. Hassan; Jasim H. Kadhum; Xiu-Qun Yang (Al-Mustansiriyah Journal of Science)
Background: Semi-arid regions of the world experience diverse climates and weather events, including dust storms. These storms suspend and transport particles in the atmosphere. Objective: The Iraqi Meteorological Organization and Seismology (IOM) is a key data source for researchers studying these dynamics, offering visibility data for Baghdad from several years (2005, 2008, 2009, 2011, 2018, 2022). Baghdad’s data is also included in the ERA-5 dataset from the European Centre for Medium-Range Weather Forecasts (ECMWF), which provides precise hourly air temperature data at 2 meters above ground level. Methods: The study investigates the correlation between air temperature and dust storm severity in semi-arid regions, particularly during storm waves, which can constitute up to half of a storm’s duration. The severity of dust storms, influenced by temperature variations, is crucial in understanding storm characteristics. Results: The findings underscore the significance of air temperature in understanding dust storms’ behavior, aiding in refining forecasting models and emergency planning in vulnerable areas. The detailed spatial and temporal data from the study provide a foundation for in-depth research into the complexities of dust storms. Conclusions: By analyzing visibility and temperature records, the study emphasizes the role of climatic factors in shaping dust storm behavior in semi-arid regions.